METHODS FOR DEVELOPING FLUENT SPEECH IN PRESCHOOL CHILDREN (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article explores the methods for developing fluent speech in preschool children, emphasizing the importance of early speech development in their cognitive, emotional, and social growth. Fluent speech allows children to express their thoughts and ideas clearly, which is essential for effective communication and social interaction. The article outlines several key methods for promoting fluent speech, including storytelling, language games, the use of multimedia, encouraging dialogues, and regular reading. It also discusses the significance of a language-rich environment and the role of social interaction in speech development. Additionally, the article addresses the importance of early intervention in cases of speech delays, highlighting the role of speech therapists in providing targeted support. Overall, the article provides practical strategies for educators and caregivers to foster fluent speech in young children, laying the foundation for effective communication in their future lives.